A woman’s search for refuge in Shashi Deshpande’s The Dark Holds No Terrors - Kumari, Y. Kusuma; Kumar, P.V.Ravi (International Journal of Psychosocial Rehabilitation, 2020)
Shashi Deshpande is incomparable for her portrayal of Indian middle-class educated women with their turmoil and frustrations and for the long silence, which has been their lot for centuries in the past. In all her novels, the problems confronted by the protagonists are almost the similar issue, namely, their search for self- identity which to a greater extent emancipates them from the suffocating problem of being stifled under the weight of man’s hegemony or male chauvinism. The central theme of her novels seems to be the search for individual autonomy and self-realization in the web of family relations. Seeing the educated middle class women caught up between the restrictive forces of patriarchal family system and male-chauvinism, she creates her protagonists as characters facing many odds and confronting many an impediment in their way of finding out some exit. Her characters are made to pass through many trials and tribulations, before they emerge with aplomb and supreme self-confidence and finally stand on their own feet. Deshpande believes that her protagonists have potential or talent in a dormant stage and they must explore new opportunities to sustain themselves and thus they must discover their own identity. Deshpande does not believe in the theory that “Women Are Victims”. She believes that the ‘dependency syndrome’ in women is responsible for their victimization. Her feminism is pro-woman but it is not anti-man.